Assessment of Food Wastage in Hostel Messes – An Exploratory Qualitative Study - M. Rajalakshmi; S. Harshavardhini (Journal of Medical Evidence)
Introduction: The level of food waste must be assessed to ensure food security, as increasing agricultural productivity alone will not be sufficient. A common contributor to food waste is unintentionally heaping the plate with more food than is intended. In areas with a mass group and an endless supply of food, like a hostel mess, the amount of food wasted rises drastically. Thus, we planned to explore the reasons of food wastage amongst the resident students in the hostel mess and to know the possible solutions to reduce its waste. Methodology: It was a qualitative exploratory study carried out amongst 50 students residing in girls’ and boys’ hostel of tertiary care teaching hospital. Informed consent was taken from all the study participants. Free listing was done to find the reasons and possible solutions of food wastage with validated interview guide. The data were entered and analysed using Visual Anthropac software. Results: The three categories emerged from the reasons of food wastage were student-related factors, mess staff-related factors and management-/warden-related factors. The most salient student-related factors voted for food wastage were 20% ordering food from outside without prior intimation, 15% said that they deliberately waste food as they paid for it, 60% of the participants felt that the taste of the food was not up to the level and 45% proclaimed that cooking more food than required. The management-related factors were monotonous menu (35%). Conclusion: Despite surplus food production wastage of food occurs due to the lethargic behaviour of everyone on food wastage. It is imperative for each one of us to judiciously consume food which is required which solves half of the problems of wastage and the unmanageable wasting can be used to create energy or other purposes in order to prevent complete wastage and produce energy.